2012
DOI: 10.1007/s10840-011-9641-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of left atrial volume measured by non-invasive cardiac imaging in the treatment of paroxysmal atrial fibrillation

Abstract: The assessment of LA size should not be incorporated as a main factor with regard to predicted ablation success in patients with paroxysmal AF being considered for PVI, as PVI may be successful even with considerable LA enlargement. Ablation should be performed promptly in patients with LAV ≤ 95 ml to prevent further LA dilatation, as patients with LAV >95 ml have an increased probability to develop persistent AF in the case of ablation failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Large left atrial (LA) size was found to be a predictor of recurrence of AF after electrical or pharmacological cardio-version as well as after ablative treatment [14][15][16][17]. The prognostic value of volume seems to be absent in AFparox, however [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large left atrial (LA) size was found to be a predictor of recurrence of AF after electrical or pharmacological cardio-version as well as after ablative treatment [14][15][16][17]. The prognostic value of volume seems to be absent in AFparox, however [18].…”
Section: Discussionmentioning
confidence: 99%
“…Large left atrial (LA) size was found to be a predictor of recurrence of AF after electrical or pharmacological cardio-version as well as after ablative treatment [14][15][16][17]. The prognostic value of volume seems to be absent in AFparox, however [18].LA function comprises three phases: reservoir, conduit and active contraction phase [19]. LA-active function increases with slight volume load as long as LA structural dilatation is limited [19,20].…”
mentioning
confidence: 99%
“…The reported predictors of recurrence after ablation are the presence of hypertension, long duration of AF, prolonged procedural time, enlarged LA diameter (LAD), or increased LA volume (LAV) and decreased LA function. [4][5][6][7][8][9] However, there is no consensus regarding the risk factors for recurrence because of heterogeneities in the study population, differences in the follow-up period, and differences in the type of AF.Echocardiography has a well-recognized and essential role in the current guidelines for the assessment of cardiac structure and function in patients with AF.10) Several echocardiographic parameters for predicting the maintenance of SR after cardioversion, including LA size, mitral A wave velocity, and left atrium and LA appendage (LAA) mechanical function 11-13) have been reported. However, these echocardiographic predictors of AF recurrence have only been evaluated during a relatively short-term follow-up period.…”
mentioning
confidence: 99%
“…The reported predictors of recurrence after ablation are the presence of hypertension, long duration of AF, prolonged procedural time, enlarged LA diameter (LAD), or increased LA volume (LAV) and decreased LA function. [4][5][6][7][8][9] However, there is no consensus regarding the risk factors for recurrence because of heterogeneities in the study population, differences in the follow-up period, and differences in the type of AF.…”
mentioning
confidence: 99%
“…11,12 Indexed LA volume (LAV) was shown to be strongly associated with AF recurrence after catheter ablation in a cohort of patients with paroxysmal and persistent AF. 13,14 Among the tissue Doppler imaging (TDI) parameters, the E/E' is the key parameter in the estimation of the degree of diastolic dysfunction and this parameter was evaluated for AF recurrence after electrical cardioversion 15 and catheter ablation. 11 Based on these results, there is no single echo parameter which can be able to clearly predict AF occurrence and identify patients who will benefit from catheter ablation.…”
Section: Introductionmentioning
confidence: 99%